Great Northern War and Church reform of Peter the Great - N. V. Sokolova (Vestnik MGIMO-Universiteta, 2021)
The article presents historical research on the Church reform of Peter I, considering the Great Northern War (1700–1721) as one of the crucial transformational factors in church-state relations in Russia. The article introduces descriptive books of patriarchal estates in 17 counties of Russia. They were created during the audit of Church and monastic property in line with the decree of January 31, 1701. It considers features of the form and content of these documents and previously known descriptions of bishops' houses and monasteries, which were carried out according to the mandated memorials of the Monastic Order in 1701-1705. The article claims that the secularization of the patriarch's landholdings, in contrast to other church holdings, was complete and final already at the beginning of the 18th century. In this regard, there is an obvious need to reject historical parallels between the events of the early 18th century and the "monastic secularization" of 1764.Comparing the Alexei Kurbatov’s proposals to Peter I in a letter dated October 25, 1700, with the content of the personal decrees of January 24 and 31, 1701 on the restoration of the Monastic Order allows us to hypothesize that the defeat at Narva and preparation for the meeting with the Elector Augustus II that would result in the signing of the Biržai pact, significantly adjusted the plans of the Church reform. The novelty of the January decrees that presumably started the reform (in the then-common European sense of the concept) was the inclusion of the patriarch's estates in the list of the Church's possessions subject to the control of the state in the future.I conclude that the secularization of church-monastic possessions and property that followed at the beginning of the Great Northern War not only contradicted the centuries-old historical practice but was at that time organizationally overwhelming for the state, which was able to solve the problem of managing the escheat patriarchal lands but did not yet have the appropriate staffing and logistics capacities for control over all possessions of the Church.